2022
DOI: 10.1021/jacs.1c10973
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Lewis Basic Sites into a Stable Ethane-Selective MOF Enabling One-Step Separation of Ethylene from a Ternary Mixture

Abstract: Purification of C 2 H 4 from a ternary C 2 H 2 /C 2 H 6 /C 2 H 4 mixture by one-step adsorption separation is of prime importance but challenging in the petrochemical industry; however, effective strategies to design high-performance adsorbents are lacking. We herein report for the first time the incorporation of Lewis basic sites into a C 2 H 6 -selective MOF, enabling efficient one-step production of polymer-grade C 2 H 4 from ternary mixtures. Introduction of amino groups into highly stable C 2 H 6 -selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
142
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(147 citation statements)
references
References 90 publications
5
142
0
Order By: Relevance
“…Recently, Li et al. reported the incorporation of Lewis basic sites into a C 2 H 6 ‐selective MOF (UiO‐67 (NH 2 ) 2 ), enabling efficient one‐step production of polymer‐grade C 2 H 4 from C 2 H 2 /C 2 H 4 /C 2 H 6 mixtures [10h] . From the viewpoints in these results, the construction of novel MOFs that selectively adsorb C 2 H 2 and C 2 H 6 over C 2 H 4 is expected not only to be used to solve the separation of multi‐component gas mixtures, but also to facilitate the understanding of specific gas molecule binding sites in MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Li et al. reported the incorporation of Lewis basic sites into a C 2 H 6 ‐selective MOF (UiO‐67 (NH 2 ) 2 ), enabling efficient one‐step production of polymer‐grade C 2 H 4 from C 2 H 2 /C 2 H 4 /C 2 H 6 mixtures [10h] . From the viewpoints in these results, the construction of novel MOFs that selectively adsorb C 2 H 2 and C 2 H 6 over C 2 H 4 is expected not only to be used to solve the separation of multi‐component gas mixtures, but also to facilitate the understanding of specific gas molecule binding sites in MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…The C 2 H 2 /C 2 H 4 and C 2 H 6 /C 2 H 4 selectivity was calculated to be 1.82 and 1.15 at 298 K according to the ideal adsorption solution theory (IAST). 46 The adsorption selectivity and Q st for 26 NUM-9a (1.5), 30 Azole-Th-1, 31 NPU-1 (1.4), 32 UiO-67-(NH 2 ) 2 (2.1), 28 and Zn-atz-oba (1.43). 34 To promote C 2 H 6 /C 2 H 4 selectivity and ternary separation performance, we extended the conjugation of the linker to enhance the C-H/p interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al recently reported MOFimmobilized basic sites to promote the C 2 H 2 /C 2 H 4 selectivity. 28 Incorporation of open metal sites could potentially enhance the acetylene adsorption to promote the C 2 H 2 /C 2 H 4 selectivity, and subsequently maximize the overall separation performance, which has rarely been reported. 29 Herein, we report two isostructural MOFs with unique open nickel sites, BUT-150 (Ni 2 (m 2 -OH 2 )DiBP 4 , DiBP ¼ 5,5ʹ-([2,2 0bipyridine]-5,5 0 -diyl)diisophthalate) and BUT-151 (Ni 2 (m 2 -OH 2 ) DiPhen 4 , DiPhen ¼ 5,5ʹ-(1,10-phenanthroline-3,8-diyl) diisophthalate).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the case of ethane/ethylene separation, which has almost similar chemical and physical properties, researchers have shown that polar groups such as sulfonate, peruoro and amino groups help in the separation of these light hydrocarbons. [41][42][43] Different functional groups are also used to introduce hydrophobicity in the structure. For example, small alkane chains have been used to introduce hydrophobicity into MOFs, allowing for much better hydrostability.…”
Section: Tuning By Ligand Controlmentioning
confidence: 99%